Revitalization Village Digital Community Space (RKDD) and Establishment of Digital Corner to Realize a Bumi Harjo as a Smart Village - Almustari A. Enteding; Yuliana Mangendre; Muhlin Muhlin; Nurlaela Nurlaela (Dinasti Publisher, 2025)
Bumi Harjo village is one of villages in Moilong sub-district, Banggai Regency, Central Celebes Province, which has been designated as one of the 1000 smart villages in Indonesia. The government’s initiative in this regard was to establish a Village Digital Community Space (RKDD) in each smart village, include in Bumi Harjo. The village government had high hopes for the development of RKDD; however the RKDD did not develop effectively. Therefore, the community service team took steps to assist Bumi Harjo Village Government to realizing their expectations regarding the development of RKDD through of the Revitalization Village Digital Community Space (RKDD) and Establishment of Digital Corner to Realize a Bumi Harjo as a Smart Village. The method used in community service project was Participatory Action research (PAR), an empowerment-oriented approach that addresses to community needs and solves practical problems. The result of this project showed the establishment of a village website based on public services, the improvement of RKDD members’ ability to manage village websiate and social media, and the creation of Digital Corner.